Review of the Urban Carbon Flux and Energy Balance Based on the Eddy Covariance Technique - Yuxuan Li; Xinli Cai; Mingjun Li; Zhen Jiang; Feifei Tang; Shaojie Zhang; Taotao Shui; Shuguang Zhu (Aerosol and Air Quality Research)
Abstract In recent years, notable climate change has prompted more scholars to give more attention to urban climate development. Recognized as the most accurate flux measurement method, the eddy covariance (EC) technique is widely used in the direct observation of CO2 and energy fluxes. Therefore, to better summarize and describe relevant research, this paper was based on all 127 studies in the Web of Science (WOS) that employed the EC technique to observe urban CO2 and energy fluxes and related auxiliary research from 2009 to 2022, and we further selected other classic studies to provide theoretical support to analyze CO2 fluxes, radiation, sensible heat, latent heat, anthropogenic heat and storage heat, which from the two aspects of the CO2 fluxes and surface energy balance (SEB). The variation characteristics of CO2 and energy fluxes were obtained by comparing observation data from various regions at different time scales, and the mechanism of flux change was explained based on the main influencing factors, thereby providing a general summary of the impact of urban heterogeneity. The results show that carbon emissions in urban areas are highly cyclical and vary greatly at different times and seasons. Due to the many factors affecting urban carbon emissions, urban carbon reduction cannot be limited to vegetation research. In addition, the heterogeneity of the underlying surface in urban areas has a great influence on the energy flux parameters. Therefore, it is necessary to improve the energy calculation models to more accurately assess SEB in urban areas. And the long-term observations at different locations are needed. In addition, Python and other means were used to analyze the occurrence frequency of important research objects and methods in the literature, and the research hotspots and correlations between regions were visualized, which enables readers to better understand the field of urban climate.